2022
DOI: 10.1111/sms.14243
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary blood doping—Performance, mechanism, and detection

Abstract: Blood doping is prohibited for athletes but has been a well‐described practice within endurance sports throughout the years. With improved direct and indirect detection methods, the practice has allegedly moved towards micro‐dosing, that is, reducing the blood doping regime amplitude. This narrative review evaluates whether blood doping, specifically recombinant human erythropoietin (rhEpo) treatment and blood transfusions are performance‐enhancing, the responsible mechanism as well as detection possibilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 113 publications
(327 reference statements)
0
10
0
Order By: Relevance
“…A consensus appears to exist in the perception that applying direct as well as biomarker-based indirect test methods (as provided, e.g., by the ABP hematological module) enables the identification of doping practices while clearly recognizing biomarker variabilities originating from factors other than doping. However, the consensus extends also to the observation that new, complementary biomarkers would be beneficial to enhance the sensitivity of the ABP, [158][159][160]…”
Section: Manipulation Of Blood and Blood Componentsmentioning
confidence: 99%
“…A consensus appears to exist in the perception that applying direct as well as biomarker-based indirect test methods (as provided, e.g., by the ABP hematological module) enables the identification of doping practices while clearly recognizing biomarker variabilities originating from factors other than doping. However, the consensus extends also to the observation that new, complementary biomarkers would be beneficial to enhance the sensitivity of the ABP, [158][159][160]…”
Section: Manipulation Of Blood and Blood Componentsmentioning
confidence: 99%
“…77 Included in the ABP, the 14 current variables of the hematological module remain the only biomarkers actually used for the indirect detection of blood doping. 152 However, although numerous studies confirmed the sensitivity of the ABP to multiple blood doping protocols, [153][154][155] the hematological module of the ABP has shown its limitation to identify rhEPO microdoses 156 and direct detection opportunities remain possible. 14 In addition, consistently adjusted by the body, plasma volume (PV) plays a key role in the variability of many markers of the ABP, 157 especially on [Hb] and the resulting OFF score.…”
Section: Metabolomic Analysesmentioning
confidence: 99%
“…For instance, the Abnormal Blood Profile Score or the ON/OFF scores have been specially designed to identify the early days and cessation phases of rhEPO intake 77 . Included in the ABP, the 14 current variables of the hematological module remain the only biomarkers actually used for the indirect detection of blood doping 152 . However, although numerous studies confirmed the sensitivity of the ABP to multiple blood doping protocols, 153–155 the hematological module of the ABP has shown its limitation to identify rhEPO microdoses 156 and direct detection opportunities remain possible 14 .…”
Section: Hematological Variablesmentioning
confidence: 99%
“…CBC is a rapid and relatively inexpensive method that offers important information regarding the diagnosis of different pathologies or conditions. Notably CBC, and [Hb], can be used to detect athletes using blood doping to increase their performance (3,4), to identify individuals at risk of stroke in vulnerable populations (5,6), to help patients hospitalization decision (7) or to regulate patient blood management (PBM) (8)(9)(10). But most importantly, CBC is used to diagnose hemoglobin disorders such as anemia.…”
Section: Introductionmentioning
confidence: 99%